Diagnostic services in oncology: The problem of scarce resources - Maria Węgrzyn (Economic and Environmental Studies (E&ES), 2019)
The high dynamics of growth in cancer incidence in Poland, coupled with the low survavility rate, is a strong indication of an ineffective approach to the problem at hand and poses a great challenge for public administration bodies. Problems arise not only in the context of systemic organisation of the oncologic treatment process as such, but also in the availability of diagnostic procedures and the capabilities of financing this type of services. The paper examines the cost of diagnostic radiology procedures (PET scans) against the funds assigned for this purpose from the public health care system (National Health Fund - NFZ), with the purpose of evaluating the public accessibility of diagnostic services in oncology. The conclusions are supplemented by analyses of the initial results brought about by the recent systemic reform of the so-called 'oncology package'. The paper presents an explanatory approach based on diagnostic and replicative methods of research. This line of enquiry served to confirm the present development trends in the area of diagnostic oncologic services, and provided suggestions for the most crucial amendmends and revisions of the existing system.
Keywords: I12; I15; I18; 330; financing health prophylactics; cost of diagnostic services; health security